Hubungan Tingkat Kepatuhan Minum Obat Dengan Kadar Gula Darah Puasa Pasien Diabetes Melitus - Rosadi, Erik; Putri, Anggy Utama; Arif, Ahmad (JURNAL KESEHATAN TERAPAN, 2025)
Diabetes Mellitus (DM) is a health problem of global concern. DM is included in a group of metabolic diseases which are characterized by an increase in blood sugar levels due to inability to produce insulin or impaired insulin performance. The aim of this study was to determine whether there was a relationship between the level of adherence to taking medication and fasting blood sugar levels. A cross-sectional design was used in this study to collect independent and dependent variables simultaneously. Chi-square was used for statistical tests. This research used a sample of 53 people. In this review, based on the Chi-Square factual test, it was obtained that P-value = 0.000 < 0.05, it can be concluded that there is a significant relationship between the level of adherence to taking medication and fasting blood sugar levels at the Kertapati Community Health Center, Palembang City